Chronic Kidney Diseases, Metabolic Syndrome and Crp Level in The Elderly Residents of Kahrizak Charity Foundation - Hossein Fakhrzadeh; Maryam Ghaderpanahi; Farshad Sharifi; AhmadAli Akbari Kamrani; Zohre Badamchizade; Mojde Mirarefin; Robabe Sahhaf (University of Social Welfare & Rehabilitation Sciences, 2010)
Objectives: In this study, we investigated the inter-relationships between C-reactive protein, metabolic syndrome, and chronic kidney disease among a group of Iranian elderly. Methods & Materials: In this cross-sectional study, 122 elderly among 1220 aged residents of Kahrizak Charity foundation with average age of 73.6±9.71 were studied. Metabolic syndrome and chronic kidney diseasewere defined according to the criteria of National Cholesterol Education Program,Adult Treatment Panel III and an estimated glomerular filtration rate<60 mL/min/1.73 m2, respectively. C-reactive protein≥3mg/dl was considered as a high CRP. Results: Prevalence of Chronic Kidney Disease was 82.9(59.3%) in subjects with and without metabolic syndrome, respectively (P<0.006). Subjects with metabolic syndrome and high C-reactive protein had 1.71-fold greater odds of having Chronic Kidney Disease. Conclusion: Metabolic syndrome was a risk factor for chronic kidney disease in elderly people of this study. The odds of chronic kidneydisease also increased significantly in presence of high C-reactive protein and metabolic syndrome.